Dual action of BPC194: a membrane active peptide killing bacterial cells - Moiset, Gemma; Cirac, Anna D.; Stuart, Marc C. A.; Marrink, Siewert-Jan; Sengupta, Durba; Poolman, Bert (Plos One, 2013)
Membrane active peptides can perturb the lipid bilayer in several ways, such as poration and fusion of the target cell membrane, and thereby efficiently kill bacterial cells. We probe here the mechanistic basis of membrane poration and fusion caused by membrane-active, antimicrobial peptides. We show that the cyclic antimicrobial peptide, BPC194, inhibits growth of Gram-negative bacteria and ruptures the outer and inner membrane at the onset of killing, suggesting that not just poration is taking place at the cell envelope. To simplify the system and to better understand the mechanism of action, we performed Forster resonance energy transfer and cryogenic transmission electron microscopy studies in model membranes and show that the BPC194 causes fusion of vesicles. The fusogenic action is accompanied by leakage as probed by dual-color fluorescence burst analysis at a single liposome level. Atomistic molecular dynamics simulations reveal how the peptides are able to simultaneously perturb the membrane towards porated and fused states. We show that the cyclic antimicrobial peptides trigger both fusion and pore formation and that such large membrane perturbations have a similar mechanistic basis.

Differential dynamics of the serotonin(1A) receptor in membrane bilayers of varying cholesterol content revealed by all atom molecular dynamics simulation - Patra, Swarna M.; Chakraborty, Sudip; Shahane, Ganesh; Prasanna, Xavier; Sengupta, Durba; Maiti, Prabal K.; Chattopadhyay, Amitabha (Molecular Membrane Biology, 2015)
The serotonin(1A) receptor belongs to the superfamily of G protein-coupled receptors (GPCRs) and is a potential drug target in neuropsychiatric disorders. The receptor has been shown to require membrane cholesterol for its organization, dynamics and function. Although recent work suggests a close interaction of cholesterol with the receptor, the structural integrity of the serotonin(1A) receptor in the presence of cholesterol has not been explored. In this work, we have carried out all atom molecular dynamics simulations, totaling to 3s, to analyze the effect of cholesterol on the structure and dynamics of the serotonin(1A) receptor. Our results show that the presence of physiologically relevant concentration of membrane cholesterol alters conformational dynamics of the serotonin(1A) receptor and, on an average lowers conformational fluctuations. Our results show that, in general, transmembrane helix VII is most affected by the absence of membrane cholesterol. These results are in overall agreement with experimental data showing enhancement of GPCR stability in the presence of membrane cholesterol. Our results constitute a molecular level understanding of GPCR-cholesterol interaction, and represent an important step in our overall understanding of GPCR function in health and disease.
Keywords: GPCR; Membrane cholesterol; molecular dynamics simulation; serotonin(1A) receptor

Dynamics of loops at the substrate entry channel determine the specificity of iridoid synthases - Sandholu, Anand S.; Mohole, Madhura; Duax, William L.; Thulasiram, Hirekodathakallu V.; Sengupta, Durba; Kulkarni, Kiran (Febs Letters, 2018)
Iridoid synthases belong to the family of short-chain dehydrogenase reductase involved in the biosynthesis of iridoids. Despite having high sequence and structural homology with progesterone 5 beta- reductase, these enzymes exhibit differential substrate specificities. Previously, two loops. L1 and L2 at substrate-binding pocket, were suggested to be involved in generating substrate specificity. However, the structural basis of specificity determinants was elusive. Here, combining sequence and structural analysis, site-directed mutagenesis, and molecular dynamics simulations, we have shown that iridoid synthase contains two channels for substrate entry whose geometries are altered by L1-L2 dynamics, primarily orchestrated by interactions of residues Glu161 and Gly162 of L1 and Asn358 of L2. A complex interplay of these interactions confer the substrate specificity to the enzyme.
Keywords: iridoid synthase; iridoids; Molecular dynamics simulations; progesterone 5 beta-reductase; Substrate specificity

Differential dynamics underlying the Gln27Glu population variant of the beta(2)-adrenergic receptor - Bhosale, Sumedha; Nikte, V. Siddhanta; Sengupta, Durba; Joshi, Manali (Journal of Membrane Biology, 2019)
The beta (2)-adrenergic receptor (beta (2)AR) is a membrane-bound G-protein-coupled receptor and an important drug target for asthma. Clinical studies report that the population variant Gln27Glu is associated with a differential response to common asthma drugs, such as albuterol, isoproterenol and terbutaline. Interestingly, the 27th amino acid is positioned on the N-terminal region that is the most flexible and consequently the least studied part of the receptor. In this study, we probe the molecular origin of the differential drug binding by performing structural modeling and simulations of the wild-type (Gln) and variant (Glu) receptors followed by ensemble docking with the ligands, albuterol, isoproterenol and terbutaline. In line with clinical studies, the ligands were observed to interact preferentially with the Glu variant. Our results indicate that the Glu residue at the 27th position perturbs the network of electrostatic interactions that connects the N-terminal region to the binding site in the wild-type receptor. As a result, the Glu variant is observed to bind better to the three ligands tested in this study. Our study provides a structural basis to explain the variable drug response associated with the 27th position polymorphism in the beta (2)AR and is a starting step to identify genotype-specific therapeutics.
Keywords: beta(2)-Adrenergic receptor; G-protein-coupled receptor; GPCR; molecular dynamics; Pharmacogenetics; SNP

Dynamic protein interfaces and conformational landscapes of membrane protein complexes - Kharche, Shalmali A.; Sengupta, Durba (Current Opinion in Structural Biology, 2020)
Dynamic interactions between membrane proteins span a range of spatio-temporal scales and determine several cellular outcomes. Experimental methods in structure determination are able to resolve static protein-protein complexes at the membrane, but lack the resolution required for disordered, flexible domains and dynamic interactions. Computational approaches could bridge the resolution gap and help to unravel molecular details underlying these crucial interactions. Here, we review current approaches to predict dynamic membrane-protein complexes, with a focus on G protein-coupled receptors (GPCRs). Ensemble coarse-grain simulations have captured the conformational heterogeneity of several membrane receptor complexes. In conjunction, the conformational plasticity of protein interfaces especially encompassing unstructured domains is well represented by atomistic simulations. A combined integrative approach will pave the way forward to understand the molecular details of these dynamic complexes.

Dynamic coupling analysis on plant sesquiterpene synthases provides leads for the identification of product specificity determinants - Singh, Sneha; Thulasiram, V, Hirekodathakallu; Sengupta, Durba; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2021)
Sesquiterpene synthases catalyse cyclisation of farnesyl pyrophosphate to produce diverse sesquiterpenes. Despite utilising the same substrate and exhibiting significant sequence and structural homology, these enzymes form different products. Previous efforts were based on identifying the effect of divergent residues present at the catalytic binding pocket on the product specificity of these enzymes. However, the rationales deduced for the product specificity from these studies were not generic enough to be applicable to other phylogenetically distant members of this family. To address this problem, we have developed a novel approach combining sequence, structural and dynamical information of plant sesquiterpene synthases (SSQs) to predict product modulating residues (PMRs). We tested this approach on the SSQs with known PMRs and also on sesquisabinene synthase 1 (SaSQS1), a SSQ from Indian sandalwood. Our results show that the dynamical sectors of SSQs obtained from molecular dynamics simulation and their hydrophobicity and vicinity indices together provide leads for the identification of PMRs. The efficacy of the technique was tested on SaSQS1 using mutagenesis. To the best of our knowledge, this is a first technique of this kind which provides cues on PMRs of SSQs, with divergent phylogenetic relationship. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: molecular dynamics; Product specificity; Sesquiterpene synthases; Statistical coupling analysis; X-ray crystallography

Differential membrane curvature induced by distinct protein conformers - Malshikare, Hrushikesh; Prakash, Shikha; Sengupta, Durba (Soft Matter, 2023)
Membrane topology changes are associated with various cellular processes and are modulated by synergistic effects between lipid composition and membrane-associated proteins. However, how protein shape or conformational dynamics couples to membrane molecular properties remains unclear. In this work, we aim to investigate this coupling behavior using the curvature-inducing protein caveolin-1. We considered distinct protein conformers of the helical hairpin protein corresponding to different protein shapes, such as the wedge and the banana-shaped conformers. The different protein conformers were simulated in a coarse-grain representation in the presence of cholesterol-sphingomyelin rich membrane. We observed that membrane curvature is dependent on protein shape and is the lowest for the wedge conformer and maximal for the banana conformer. The differences in the net stress between the two membrane leaflets, calculated from the lateral pressure profile distributions in lipid bilayers for different protein conformers, show a similar trend. In conjunction, we show that cholesterol and sphingomyelin clustering in the membrane is modulated by protein shape. Overall, our results provide molecular-level insights into the coupling between membrane topology, protein shape and lipid clustering in cell membranes.

Dynamic structure of the lipid bilayer and its modulation by small molecules - Sengupta, Durba; Huster, Daniel (Journal of Physical Chemistry B, 2025)